(untitled) (Journal of the College of Basic Education, 2022)
The great progress witnessed by the era in the scientific and technical field requires preparing students well to be able to rely on themselves through the continuation of the abundant flow of information and knowledge that invaded all fields of life, including the fields of education, which made modern trends emphasize the care of education and its methods. And that the main goal of the educational process is to achieve the educational and educational goals, the most important of which is to reach students’ mastery of most of the cognitive and technical skills in the light of successive educational and psychological research in the fields of study and fields of education.